INOVASI PEMBELAJARAN UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MDTA AN-NUUR - Suriyah; Siti Fatimah Siregar; Paridah Hanum Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the learning innovations implemented at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) An-Nuur and its impact on improving the quality of education. Learning innovation is an effort to improve and develop learning methods and strategies to be more effective and efficient in achieving educational goals. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and document analysis. The results of the study indicate that the learning innovations implemented at MDTA An-Nuur, such as the use of technology in learning, the application of active learning methods, and the development of competency-based curriculum, can significantly improve the quality of education. Students showed an increase in learning motivation, critical thinking skills, and understanding of subject matter. This study suggests that learning innovations continue to be developed and adjusted to student needs and technological developments to achieve better quality of education.